1992
DOI: 10.1126/science.11537889
|View full text |Cite
|
Sign up to set email alerts
|

Water in SNC Meteorites: Evidence for a Martian Hydrosphere

Abstract: The Shergotty-Nakhla-Chassigny (SNC) meteorites, purportedly of martian origin, contain 0.04 to 0.4 percent water by weight. Oxygen isotopic analysis can be used to determine whether this water is extraterrestrial or terrestrial. Such analysis reveals that a portion of the water is extraterrestrial and furthermore was not in oxygen isotopic equilibrium with the host rock. Lack of equilibrium between water and host rock implies that the lithosphere and hydrosphere of the SNC parent body formed two distinct o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(82 citation statements)
references
References 22 publications
4
78
0
Order By: Relevance
“…Martian silicate itself has 17 O = +0.3‰ compared to the terrestrial fractionation line (Franchi et al, 1999). The data of Farquhar and Thiemens is similar to that of Karlsson et al (1992) who showed that water in the SNC meteorites had 17 O greater than that of the anhydrous silicates by values up to 17 O = +0.6‰ (Nakhla) although Shergotty and EETA 79001 showed no 17 O excesses over their whole rock values.…”
Section: Oxygensupporting
confidence: 67%
See 3 more Smart Citations
“…Martian silicate itself has 17 O = +0.3‰ compared to the terrestrial fractionation line (Franchi et al, 1999). The data of Farquhar and Thiemens is similar to that of Karlsson et al (1992) who showed that water in the SNC meteorites had 17 O greater than that of the anhydrous silicates by values up to 17 O = +0.6‰ (Nakhla) although Shergotty and EETA 79001 showed no 17 O excesses over their whole rock values.…”
Section: Oxygensupporting
confidence: 67%
“…In this model, the water has the same 17 O as the silicate. However, the discovery that water and secondary minerals in ALH84001, Nakhla and Lafayette have 17 O in excess of the host rock (Karlsson et al, 1992; implies that not only the carbonates, but also the waters from which they formed were not equilibrated with the parent rocks. Saxton et al (1998) considered several models for the formation of the ALH84001 carbonates.…”
Section: Oxygenmentioning
confidence: 99%
See 2 more Smart Citations
“…Martian silicate itself has 17 O = +0.3‰ compared to the terrestrial fractionation line (Franchi et al, 1999). The data of Farquhar and Thiemens is similar to that of Karlsson et al (1992) Temperature and isotopic fractionation constraints from oxygen: Carbonate equilibrated with silicate at 500−700…”
Section: Oxygensupporting
confidence: 65%